Key challenges to voluntary medical male circumcision uptake in traditionally circumcising settings of Machinga district in Malawi - Rodney Masese; Gertrude Mwalabu; Pammla Petrucka; Patrick Mapulanga (BMC, 2021)
Abstract Background Voluntary medical male circumcision (VMMC) is becoming more popular as an important HIV prevention strategy. Malawi, with a high HIV and AIDS prevalence rate of 8.8% and a low male circumcision prevalence rate of 28% in 2016, is one of the priority countries recommended for VMMC scale-up. This paper investigates the attitudes and key challenges to VMMC adoption in a traditionally circumcising community in Malawi where male circumcision is culturally significant. Methods A mixed design study using quantitative and qualitative data collection methods was carried out to determine the attitudes of 262 randomly selected males towards VMMC in a culturally circumcising community in Malawi. Statistical Package for the Social Sciences (SPSS) version 20 was used to analyse the quantitative data. To identify predictors of VMMC uptake, we used logistic regression analysis. To identify the themes, qualitative data were analysed using content analysis. Results The findings indicate that, while more males in this community prefer medical circumcision, traditional circumcision is still practised. Panic (63%) perceived surgical complications (31%), and cost (27%) in accessing VMMC services were some of the barriers to VMMC uptake. Age and culture were found to be statistically significant predictors of voluntary medical male circumcision in the logistic analysis. According to qualitative data analysis, the key challenges to VMMC uptake were the involvement of female health workers in the circumcision team and the incentives provided to traditional circumcisers. Conclusion According to the findings of this study, VMMC services should be provided in a culturally competent manner that respects and considers existing cultural beliefs and practices in the community. Coordination between local leaders and health workers should be encouraged so that VMMC services are provided in traditional settings, allowing for safe outcomes, and increasing VMMC uptake.